1980
DOI: 10.1084/jem.152.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Role of the major histocompatibility gene products in regulating the antibody response to dinitrophenylated poly(L-Glu55,L-Ala35,L-Phe9)n.

Abstract: These studies were carried out to investigate the potential helper T cell repertoire specific for the random copolymer poly(L-Glu55,L-Ala35, L-Phe9)n(GL phi 9) of responder, nonresponder, and (responder x nonresponder)F1 murine strains. We tested the ability of these T cells to collaborate with dinitrophenyl (DNP)-specific primary and secondary B lymphocytes of each strain in response to the antigen CNP-GL phi 9 in the splenic-fragment culture system. The results of these experiments show that there are GL phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…All stimulatory interactions require that both the T and B cells recognize the stimulating antigen, and that both determinants be on the same antigen molecule. In addition, the extensive irradiation is likely to eliminate most allogeneic stimulatory interactions (8).…”
Section: Discussionmentioning
confidence: 99%
“…All stimulatory interactions require that both the T and B cells recognize the stimulating antigen, and that both determinants be on the same antigen molecule. In addition, the extensive irradiation is likely to eliminate most allogeneic stimulatory interactions (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although such complex recognition is characteristic of T cell specificity, there have been reports that imunoglobulins can also be restricted to the recognition of certain antigenic determinants in the context of cell surface antigens (10,11). Similarly, although many studies have indicated that B cell stimulation need not be haplotype restricted (4,(27)(28)(29), a few recent investigations have implied that under certain conditions B cells may only be stimulated by antigen presented in the context of cells of an appropriate H-2 haplotype (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that nonresponder macrophages were able to present GAT to T cells as efficiently as responder macrophages were. Pierce et al (1980) reached a similar conclusion using an even more complex system of measuring the response to an antigen (DNP-GL0).…”
Section: Experiments Examining T-b Collaborationmentioning
confidence: 60%